Orçamento participativo como instrumento de gestão democrática: um estudo no Instituto Federal da Paraíba - Gonçalves, Emeline Maria Santana Benjamin (2021)
This research aims to make a diagnosis about the Participatory Budget at the Instituto Federal da Paraíba (IFPB) João Pessoa's Campus. For this, we conducted a literature review understanding Public Budgeting; Participatory Budgeting; Participative Budget in Federal Institutions of Higher Education and the Financing of Higher Education and the Budgetary Process in IFPB. This research is configured as a case study, of qualitative approach, with descriptive objectives and that adopts bibliographic and documental research techniques. To perform the data collection and analysis, we used the content analysis technique, based on Bardin (1977), conducting an inspection of the IFPB's Institutional documents, from the period 2017 to 2019, such as the Institutional Development Plan (PDI), Institutional Self-Assessment Report (RAI), Management Report (RG), Statute (EST) and Rules of Procedure (REG) of the IFPB, in addition to public consultation, held in the current year, on the Federal Government's information access platform (Fala.BR). Through the analysis performed, it was possible to conclude that, in the period of elaboration of this research, there is no participatory budget in the IFPB João Pessoa Campus. On the other hand, it became evident that the management is open to the participation of the community in the budgeting process of the campus. Therefore, We seek to obtain results that can suggest improvements in the budget process of the IFPB João Pessoa's Campus, provide greater transparency in the allocation of resources of the institution and stimulate the practice of social control through the participation of the academic community. We also propose, based on other IFPB unit experiences, a participatory budget model for the João Pessoa's Campus IFPB.